The Speed of Adjustment Capital Structure in The Perspective of Structure-Conduct-Performance Theory - Toni Heryana; Delina Herdian Septiani; Dita Rari Dwi Rinining Tyastuty (Universitas Pendidikan Indonesia, 2023)
Main Purpose - The research objective is to explain the factors that determine the speed of capital structure adjustment based on market concentrations on profitability, company growth, liquidity, exchange rates and inflation.Method - The research method used is the explanatory method with a causality approach. The unit of analysis for this research is non-financial sector issuers listed on the Indonesia Stock Exchange in 2009-2015.Main Findings - This research finds that the structure-conduct-performance theory can be used as a theory that explains the speed of capital structure adjustment. In addition, the results of the study also found the exchange rate to be a driving factor in increasing the speed of capital structure adjustment.Theory and Practical Implications - Research findings provide support for the structure-conduct-performance theory which indicates that market concentration is a determining factor in company behavior in adjusting capital structure.Novelty - This study uses the theory of performance-behavior structure in explaining the variables that determine the speed of capital structure adjustment.